1998
DOI: 10.1177/008124639802800308
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Loneliness and the Christian Faith

Abstract: The primary aim of this study was to investigate the relationship between loneliness and the Christian faith. Questionnaires were completed by a sample of 100 third-year psychology students at the University of the Orange Free State. The results reflect a highly significant negative relationship between loneliness and the Christian faith. This may imply that the lonelier the student is, the weaker his faith is in Jesus as the Redeemer, and vice versa. These findings support the views held by many authors who m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The informants who had earlier had a close relationship with God experienced that God had either turned his back on them in their suffering, or that he had changed into a punishing God. Loneliness and religious belief are, according to le Roux (50), strongly affiliated with one another. The study shows that loneliness has a religious basis.…”
Section: Discussionmentioning
confidence: 99%
“…The informants who had earlier had a close relationship with God experienced that God had either turned his back on them in their suffering, or that he had changed into a punishing God. Loneliness and religious belief are, according to le Roux (50), strongly affiliated with one another. The study shows that loneliness has a religious basis.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of developmental psychology and psychiatric professional literature related to persons with severe psychological dysfunctions, there is a surprising lack of specific theme-focused discussion of loneliness, per se. The lack of specific studies on loneliness within the fields of professional psychology and psychiatry had already been noted in 1959 by Fromm-Reichman (32), who maintained that loneliness was one of the least satisfactorily described phenomena in psychology, and that it was indeed not even mentioned in professional psychiatric literature; the latter was later confirmed by Leidermann (33), Cohen (34) and le Roux (13). Studies in 'loneliness and psychiatry' in articles showed even less 'loneliness' as a theme.…”
Section: Loneliness In Psychological and Psychiatric Articles And Booksmentioning
confidence: 96%
“…Cultural background plays a significant role in studies of loneliness. As an example, one might mention the difficulties ethnic groups' have in readjusting, their loneliness in a new country, new schools, new social relationships, as well as their homesickness (13).…”
Section: Loneliness and Modern Societymentioning
confidence: 99%
“…Research on different dimensions of loneliness and other aspects thereof was taken into account in compiling the research instrument. This instrument has already been used in various investigations (Jordaan 2004;Le Roux 1998). The alpha coefficients were calculated in each of these studies and ranged from 0.88 to 0.91.…”
Section: The Measuring Instrumentmentioning
confidence: 99%